2013
DOI: 10.1155/2013/202534
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Short-Chain Fatty Acids, Excretion of Anthocyanins, and Microbial Diversity in Rats Fed Blackcurrants, Blackberries, and Raspberries

Abstract: Introduction. Berries contain high amounts of dietary fibre and flavonoids and have been associated with improved metabolic health. The mechanisms are not clear but the formation of SCFAs, especially propionic and butyric acids, could be important. The potent antioxidant and antimicrobial properties of flavonoids could also be a factor, but little is known about their fate in the gastrointestinal tract. Aim. To compare how blackcurrants, blackberries, raspberries, and Lactobacillus plantarum HEAL19 affect form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 59 publications
1
31
1
2
Order By: Relevance
“…DF is then available to be metabolized to oligosaccharides by the colonic microbiota, forming short chain fatty acids (SCFA) during the fermentation and resulting in the production of gases (CO 2 , CH 4 and H 2 ) and heat (Jakobsdottir et al 2013;Puertollano et al 2014;Wong & Jenkins, 2007). Acetate, propioniate and butyrate (in a ratio of 3:1:1) are the main SCFAs produced, and are well known to possess beneficial properties for host health (Cook & Sellin, 1998;Wong et al 2006) through their effects on immunoregulation, colonic gene expression, cancer, obesity, insulin resistance, metabolic regulation as well as maintaining gut and overall health (Fukuda et al 2011;Gao et al 2009;Maslowski & Mackay, 2011;Peng et al 2009;Puertollano et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DF is then available to be metabolized to oligosaccharides by the colonic microbiota, forming short chain fatty acids (SCFA) during the fermentation and resulting in the production of gases (CO 2 , CH 4 and H 2 ) and heat (Jakobsdottir et al 2013;Puertollano et al 2014;Wong & Jenkins, 2007). Acetate, propioniate and butyrate (in a ratio of 3:1:1) are the main SCFAs produced, and are well known to possess beneficial properties for host health (Cook & Sellin, 1998;Wong et al 2006) through their effects on immunoregulation, colonic gene expression, cancer, obesity, insulin resistance, metabolic regulation as well as maintaining gut and overall health (Fukuda et al 2011;Gao et al 2009;Maslowski & Mackay, 2011;Peng et al 2009;Puertollano et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Acetate, propioniate and butyrate (in a ratio of 3:1:1) are the main SCFAs produced, and are well known to possess beneficial properties for host health (Cook & Sellin, 1998;Wong et al 2006) through their effects on immunoregulation, colonic gene expression, cancer, obesity, insulin resistance, metabolic regulation as well as maintaining gut and overall health (Fukuda et al 2011;Gao et al 2009;Maslowski & Mackay, 2011;Peng et al 2009;Puertollano et al 2014). SCFA, especially butyrate, are also used as energy sources for colonocytes (Jakobsdottir et al 2013;Puertollano et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…For 5 days, rats consumed 93.9, 43.4, and 57.7 mg total anthocyanins from blackcurrant, raspberry, and blackberry respectively. They reported that blackcurrant was more potent in increasing production of SCFA compared to other berries . In another study, healthy mice fed with 20% apple flesh/peel for 7 or 21 days showed increased number of beneficial Bifidobacterium and decreased expression of inflammatory genes in jejunum tissue including IL‐2 receptor b (IL2rb), chemokine receptor‐2 (ccr2), ccr10, and decreased plasma prostaglandin E 2 (PGE 2 ) and TNF‐α levels compared to control mice .…”
Section: Impact Of Gut Microbiota On Obesity and Inflammationmentioning
confidence: 99%
“…Numerous research studies support the importance of diet rich in anthocyanins and its influence on the beneficial microbiota composition in animals …”
Section: Impact Of Gut Microbiota On Obesity and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation